A high-efficiency impurity removal and recycling process for lithium-ion batteries
By preparing high-efficiency leaching agents and performing grading and pretreatment, the problems of low impurity recovery efficiency and poor resource utilization in the existing lithium-ion battery recycling process are solved, and efficient recycling and regeneration of lithium-ion battery positive electrode materials and graphite negative electrode materials are achieved, reducing energy consumption and environmental pollution.
Patent Information
- Application Number
- CN202510028932.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing lithium-ion battery recycling process has problems such as low impurity recycling efficiency, poor resource utilization, high energy consumption, and large environmental pollution, making it difficult to efficiently recover and regenerate various types of lithium-ion battery positive electrode materials and graphite negative electrode materials.
An efficient impurity removal and recovery process is adopted, including the preparation of high-efficiency leaching agent, the grading treatment of lithium batteries, the pretreatment of negative electrode sheets and the recycling treatment of electrode sheet materials. The high-efficiency leaching agent is prepared by slowly dropping the lactic acid solution into the ammonium peroxydisulfate solution, which is used to leaching metal ions in the positive electrode material, and to improve the regeneration quality of graphite by ethylenediamine pretreatment.
It realizes efficient recycling and regeneration of various types of lithium-ion battery components, improves the leaching rate of metal ions and the regeneration quality of graphite, and reduces energy consumption and environmental pollution.
Smart Images

Figure CN119419399B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery recycling, in particular to a high-efficiency impurity removal and recycling process for lithium ion batteries. Background Art
[0002] Lithium-ion battery is a common rechargeable battery, widely used in portable electronic products, power tools, electric vehicles, energy storage systems and other fields. Compared with traditional lead-acid batteries or nickel-metal hydride batteries, lithium-ion batteries have higher energy density, longer service life and are lighter, so they have important application value in modern technology.
[0003] With the widespread application of lithium-ion batteries in consumer electronics, energy storage systems and electric vehicles, the issue of lithium battery disposal has gradually attracted attention. Waste lithium-ion batteries contain a large amount of valuable materials, such as metal elements such as lithium (Li), cobalt (Co), nickel (Ni), manganese (Mn), and negative electrode materials such as graphite. Recycling these valuable materials can not only reduce resource waste, but also reduce environmental pollution. At present, the recycling processes of lithium-ion batteries mainly include mechanical crushing, chemical leaching, incineration and physical sorting, but most methods have problems such as low impurity recovery efficiency, poor resource utilization, high energy consumption, and severe environmental pollution. Therefore, it is particularly important to develop an efficient impurity removal and recycling process. Summary of the invention
[0004] In order to solve the above technical defects, the present invention has developed a high-efficiency impurity removal and recovery process for lithium-ion batteries, which can simultaneously efficiently recycle and regenerate various types of lithium-ion battery positive electrode materials and graphite negative electrode materials, and has a high leaching rate of metal ions and good graphite regeneration quality.
[0005] A high-efficiency impurity removal and recycling process for lithium-ion batteries comprises the following steps:
[0006] S1: Preparation of efficient leaching agent;
[0007] ammonium peroxydisulfate and deionized water are mixed and magnetically stirred to prepare an ammonium peroxydisulfate solution, lactic acid is mixed and stirred with deionized water to obtain a lactic acid solution, and the lactic acid solution is slowly dripped into the ammonium peroxydisulfate solution while stirring, and after the dripping is completed, stirring is continued and the pH is adjusted to obtain a high-efficiency leaching agent;
[0008] S2: Grading of lithium batteries;
[0009] Taking different types of lithium-ion batteries to be recycled, de-charging and disassembling them to obtain plastic iron shells, positive electrode sheets, negative electrode sheets, diaphragms and a mixture containing an electrolyte, centrifuging the mixture containing the electrolyte and passing it through a mesh sieve to obtain sieved waste and organic materials, supplementing the organic materials with organic solvents and electrolyte liquid to obtain new electrolyte products, crushing the plastic iron shells and magnetically separating them to separate iron powder for recycling, heating and cleaning the diaphragms, and then melt-extruding and granulating them to recover the diaphragms, leaving the positive electrode sheets, negative electrode sheets and sieved waste for processing;
[0010] S3: pretreatment of negative electrode sheet;
[0011] The negative electrode sheet is ground and passed through a mesh sieve, then cleaned, and then evenly mixed with an ethylenediamine solution to obtain a mixed liquid, and the mixed liquid is condensed, refluxed, and heated in a nitrogen atmosphere to obtain a black powder pretreatment liquid after concentration;
[0012] S4: Recycling of pole piece materials;
[0013] The positive electrode sheet and the screened waste are mixed and ground, and then sieved to obtain positive electrode material powder. The positive electrode material powder, black powder pretreatment liquid and high-efficiency leaching agent are mixed and stirred evenly, and then heated in an oil bath. After filtering, black powder precipitate and primary leaching solution are obtained. The black powder precipitate is washed 3-4 times with deionized water and ethanol respectively to obtain regenerated graphite. Saturated sodium carbonate is added to the primary leaching solution, heated and stirred until no precipitate is generated, and lithium carbonate precipitate and ferric hydroxide are filtered and recovered to obtain secondary leaching solution. The secondary leaching solution and the extractant are mixed and heated in an oil bath, and Co, Ni, and Mn co-precipitates are filtered and recovered to obtain tertiary leaching solution. The tertiary leaching solution is treated as wastewater and then discharged.
[0014] Furthermore, the preparation of the efficient leaching agent in step S1 comprises the following steps:
[0015] S1.1: 2-3 parts by weight of ammonium peroxodisulfate are placed in a container, and then 50-60 parts by weight of deionized water are added, and magnetic stirring is performed at 25-30° C. and a stirring speed of 100-120 rpm until the solid matter in the container is completely dissolved to obtain an ammonium peroxodisulfate solution;
[0016] S1.2: Mix lactic acid and deionized water in a mass ratio of 1:(3-4) and stir evenly to obtain a lactic acid solution. Take 1.5-2 parts by weight of the lactic acid solution and put it in a dropper, then slowly drip it into the ammonium peroxydisulfate solution obtained in step S1.1, while stirring at a stirring speed of 120-150rpm. When the lactic acid is completely dripped in, continue stirring for 20-25 minutes, then add a pH adjuster to adjust the pH to 3-4 to obtain a high-efficiency leaching agent.
[0017] Furthermore, step S2 of grading the lithium battery comprises the following steps:
[0018] S2.1: Take different types of lithium-ion batteries to be recycled for de-charging and disassembly. During disassembly, first remove the plastic iron shell of the lithium-ion batteries to be recycled, then separate the positive electrode sheet, the negative electrode sheet and the diaphragm, and centrifuge the remaining mixed material containing the electrolyte and pass it through a 140-150 mesh sieve to obtain sieved waste and organic material;
[0019] S2.2: According to the composition of lithium-ion battery electrolyte, organic solvent and electrolyte liquid are added to the organic material to obtain a new electrolyte product, the plastic iron shell is mechanically crushed and magnetically separated to separate the iron powder for recycling, the diaphragm is heated to remove organic matter and adhesive impurities, and then immersed in clean water for stirring and cleaning, and then ball milling and heating, melt extrusion and granulation are carried out in sequence to recover the diaphragm, and the remaining positive electrode sheets, negative electrode sheets and screened waste are to be processed.
[0020] Furthermore, the pretreatment of the negative electrode sheet in step S3 includes the following steps:
[0021] S3.1: Grind the negative electrode plate, pass it through a 200-220 mesh sieve to obtain black powder, rinse the black powder with deionized water for 3-4 times, and then dry it at 50-60°C to obtain cleaned black powder, immerse the cleaned black powder in 3-5 times the mass concentration of 10-30% ethylenediamine solution, and stir evenly to obtain a mixed liquid;
[0022] S3.2: Transfer the mixed liquid to a container equipped with a condensation reflux device, and then pass nitrogen into the mixed liquid at a flow rate of 60-80 ml / min for 15-20 minutes, then turn on the heating device to heat at 100-150°C for 6-8 hours, and then concentrate it to 1 / 5-1 / 4 of the original volume to obtain a black powder pretreatment liquid.
[0023] Furthermore, step S4, the recovery of the pole piece material, comprises the following steps:
[0024] S4.1: The positive electrode sheet and the sieved waste are mixed and placed in a grinder for grinding, and the positive electrode material powder is obtained after passing through a 180-200 mesh sieve. The positive electrode material powder, black powder pretreatment solution and high-efficiency leaching agent are placed in a container at a mass ratio of 1: (6-10): (80-100) and stirred evenly, and then transferred to an oil bath pot and heated at 90-95°C for 1.5-2 hours, and the black powder precipitate and the primary leaching solution are obtained after filtering;
[0025] S4.2: The black powder precipitate is washed 3-4 times with deionized water and ethanol respectively to obtain regenerated graphite, 1-1.5 times the mass of the positive electrode material powder in step S4.1 is added to the primary leachate, and stirred at 50-60°C until no precipitate is generated, and the lithium carbonate precipitate and iron hydroxide are recovered by filtration to obtain a secondary leachate;
[0026] S4.3: Mix the secondary leachate and the extractant in a mass ratio of 1:(0.08-0.1) and place them in a container. Then heat them in an oil bath at 70-75℃ until no precipitate is generated. Filter and recover the co-precipitate of Co, Ni and Mn to obtain a tertiary leachate. The tertiary leachate is treated as wastewater and then discharged.
[0027] Furthermore, in step S1.2, the pH adjusting agent used to adjust the mixed solution of ammonium peroxodisulfate and lactic acid is hydrochloric acid.
[0028] Furthermore, in step S2.1, the different types of positive electrode materials of lithium-ion batteries to be recycled are lithium iron phosphate, nickel cobalt manganese and lithium cobalt oxide, and the negative electrode materials are all graphite.
[0029] Furthermore, the de-charge operation in step S2.1 is to immerse the lithium-ion battery to be recycled in a sodium chloride solution with a volume fraction of 4-6% until the voltage is less than 2V.
[0030] Furthermore, in step S4.1, the mass ratio of the nickel-cobalt-manganese positive electrode, the lithium cobalt oxide positive electrode and the lithium iron phosphate positive electrode in the positive electrode sheets disassembled from different types of lithium-ion batteries to be recycled is 1:1:(1.5-2).
[0031] Furthermore, in step S4.3, the extractant is a mixed solution of oxalic acid and ethanol in a mass ratio of 1:1.
[0032] The beneficial effects are as follows: 1. The present invention obtains an efficient leaching agent by slowly dropping a lactic acid solution into an ammonium persulfate solution. In the subsequent mixing process with the positive electrode material powder and the black powder pretreatment solution, the strong oxidizing property of the ammonium persulfate in the efficient leaching agent can achieve the leaching of lithium iron phosphate, and then the phosphorus ions are embedded in the black powder in the black powder treatment solution in a heated state, so that the graphite has a more regular carbon structure, so that the graphite black powder is regenerated while leaching metal ions, and Fe 2+ is oxidized to Fe 3+ When sodium carbonate solution is added later, it precipitates as iron hydroxide, while lactic acid leaches nickel, cobalt, manganese and lithium cobalt oxide positive electrode materials. The process is simple and can recycle a variety of waste lithium battery components at the same time. The recycling efficiency is high, and the leaching effect of each metal component is good and the leaching rate is high.
[0033] 2. The present invention grinds the negative electrode sheet and then immerses it in an ethylenediamine solution for pretreatment to obtain a black powder pretreatment solution, thereby introducing functional groups such as pyridine nitrogen and indole nitrogen on the surface of the graphite black powder, which can adsorb phosphorus elements through electrostatic adsorption and hydrogen bonds, and can enhance the ability to introduce phosphorus elements when subsequently mixed with positive electrode material powder and a high-efficiency leaching agent, so that the obtained regenerated graphite has good lithium storage performance and cycle performance, and ethylenediamine can also coordinate with subsequent metal ions to improve the leaching effect of metal components. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a flow chart of a highly efficient impurity removal and recovery process for lithium-ion batteries used in an embodiment of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0036] A highly efficient impurity removal and recycling process for lithium-ion batteries, such as Figure 1 As shown, the following steps are included:
[0037] S1: Preparation of efficient leaching agent;
[0038] S1.1: 2 parts by weight of ammonium peroxodisulfate were placed in a container, and then 50 parts by weight of deionized water were added, and magnetic stirring was performed at 25° C. at a stirring speed of 100 rpm until the solid matter in the container was completely dissolved to obtain an ammonium peroxodisulfate solution;
[0039] S1.2: Mix lactic acid and deionized water in a mass ratio of 1:3 and stir evenly to obtain a lactic acid solution. Take 1.5 parts by weight of the lactic acid solution and put it in a dropper, then slowly drop it into the ammonium persulfate solution obtained in step S1.1, while stirring at a stirring speed of 120 rpm. When the lactic acid is completely dropped in, continue stirring for 20 minutes, then add hydrochloric acid to adjust the pH to 3 to obtain a high-efficiency leaching agent.
[0040] S2: Grading of lithium batteries;
[0041] S2.1: Take different types of lithium-ion batteries to be recycled, whose positive electrode materials are lithium iron phosphate, nickel cobalt manganese and lithium cobalt oxide, and whose negative electrode materials are all graphite, immerse them in a sodium chloride solution with a volume fraction of 4% to de-charge until the voltage is less than 2V, and then disassemble them. During disassembly, first remove the plastic iron shell of the lithium-ion battery to be recycled, then separate the positive electrode sheet, the negative electrode sheet and the diaphragm, and centrifuge the remaining mixed material containing the electrolyte and pass it through a 140-mesh sieve to obtain screened waste and organic material;
[0042] S2.2: According to the composition of lithium-ion battery electrolyte, organic solvent and electrolyte liquid are added to the organic material to obtain a new electrolyte product, the plastic iron shell is mechanically crushed and magnetically separated to separate the iron powder for recycling, the diaphragm is heated to remove organic matter and adhesive impurities, and then immersed in clean water for stirring and cleaning, and then ball milling and heating, melt extrusion and granulation are carried out in sequence to recover the diaphragm, and the remaining positive electrode sheets, negative electrode sheets and screened waste are to be processed.
[0043] S3: pretreatment of negative electrode sheet;
[0044] S3.1: Grind the negative electrode plate, pass it through a 200-mesh sieve to obtain black powder, rinse the black powder three times with deionized water and dry it at 50°C to obtain cleaned black powder, immerse the cleaned black powder in 3 times the mass concentration of 10% ethylenediamine solution, and stir evenly to obtain a mixed liquid;
[0045] S3.2: The mixed liquid is transferred to a container equipped with a condensation reflux device, and nitrogen is then introduced into the mixed liquid at a flow rate of 60 ml / min for 15 minutes. The heating device is then turned on to heat at 100°C for 6 hours, and then concentrated to 1 / 5 of the original volume to obtain a black powder pretreatment liquid.
[0046] S4: Recycling of pole piece materials;
[0047] S4.1: The positive electrode sheet and the screened waste are mixed and placed in a grinder for grinding, wherein the mass ratio of the nickel-cobalt-manganese positive electrode, the lithium cobalt oxide positive electrode and the lithium iron phosphate positive electrode is 1:1:1.5, and the positive electrode material powder is obtained after passing through a 180-mesh sieve, and the positive electrode material powder, the black powder pretreatment liquid and the high-efficiency leaching agent are placed in a container at a mass ratio of 1:6:80, and stirred evenly, and then transferred to an oil bath pot and heated at 90°C for 1.5 hours, and the black powder precipitate and the primary leaching liquid are obtained after filtering;
[0048] S4.2: The black powder precipitate is washed three times with deionized water and ethanol respectively to obtain regenerated graphite, and saturated sodium carbonate with a mass of 1 times that of the positive electrode material powder in step S4.1 is added to the primary leachate, and stirred at 50°C until no precipitate is generated, and the lithium carbonate precipitate and iron hydroxide are recovered by filtration to obtain a secondary leachate;
[0049] S4.3: Mix the secondary leachate and the extractant in a mass ratio of 1:0.08 and place them in a container. The extractant is a mixed solution of oxalic acid and ethanol in a mass ratio of 1:1. Then place it in a 70°C oil bath and heat until no precipitate is generated. Filter and recover the Co, Ni, and Mn co-precipitates to obtain a tertiary leachate. The tertiary leachate is treated as wastewater and then discharged. Example
[0050] A highly efficient impurity removal and recycling process for lithium-ion batteries, such as Figure 1 As shown, the following steps are included:
[0051] S1: Preparation of efficient leaching agent;
[0052] S1.1: 3 parts by weight of ammonium peroxodisulfate were placed in a container, and then 60 parts by weight of deionized water were added, and magnetic stirring was performed at 25° C. at a stirring speed of 100 rpm until the solid matter in the container was completely dissolved to obtain an ammonium peroxodisulfate solution;
[0053] S1.2: Mix lactic acid and deionized water in a mass ratio of 1:4 and stir evenly to obtain a lactic acid solution. Take 2 parts by weight of the lactic acid solution and put it in a dropper, then slowly drop it into the ammonium persulfate solution obtained in step S1.1, while stirring at a stirring speed of 120 rpm. When the lactic acid is completely dropped in, continue stirring for 20 minutes, then add hydrochloric acid to adjust the pH to 3 to obtain a high-efficiency leaching agent.
[0054] S2: Grading of lithium batteries;
[0055] S2.1: Take different types of lithium-ion batteries to be recycled, whose positive electrode materials are lithium iron phosphate, nickel cobalt manganese and lithium cobalt oxide, and whose negative electrode materials are all graphite, immerse them in a sodium chloride solution with a volume fraction of 4% to de-charge until the voltage is less than 2V, and then disassemble them. During disassembly, first remove the plastic iron shell of the lithium-ion battery to be recycled, then separate the positive electrode sheet, the negative electrode sheet and the diaphragm, and centrifuge the remaining mixed material containing the electrolyte and pass it through a 140-mesh sieve to obtain screened waste and organic material;
[0056] S2.2: According to the composition of lithium-ion battery electrolyte, organic solvent and electrolyte liquid are added to the organic material to obtain a new electrolyte product, the plastic iron shell is mechanically crushed and magnetically separated to separate the iron powder for recycling, the diaphragm is heated to remove organic matter and adhesive impurities, and then immersed in clean water for stirring and cleaning, and then ball milling and heating, melt extrusion and granulation are carried out in sequence to recover the diaphragm, and the remaining positive electrode sheets, negative electrode sheets and screened waste are to be processed.
[0057] S3: pretreatment of negative electrode sheet;
[0058] S3.1: Grind the negative electrode plate, pass it through a 200-mesh sieve to obtain black powder, rinse the black powder three times with deionized water and dry it at 50°C to obtain cleaned black powder, immerse the cleaned black powder in 5 times the mass concentration of 10% ethylenediamine solution, and stir evenly to obtain a mixed liquid;
[0059] S3.2: The mixed liquid is transferred to a container equipped with a condensation reflux device, and nitrogen is then introduced into the mixed liquid at a flow rate of 60 ml / min for 15 minutes. The heating device is then turned on to heat at 100°C for 6 hours, and then concentrated to 1 / 5 of the original volume to obtain a black powder pretreatment liquid.
[0060] S4: Recycling of pole piece materials;
[0061] S4.1: The positive electrode sheet and the screened waste are mixed and placed in a grinder for grinding, wherein the mass ratio of the nickel-cobalt-manganese positive electrode, the lithium cobalt oxide positive electrode and the lithium iron phosphate positive electrode is 1:1:2, and the positive electrode material powder is obtained after passing through a 180-mesh sieve, and the positive electrode material powder, the black powder pretreatment liquid and the high-efficiency leaching agent are placed in a container at a mass ratio of 1:10:100, and stirred evenly, and then transferred to an oil bath pot and heated at 90°C for 1.5 hours, and the black powder precipitate and the primary leaching liquid are obtained after filtering;
[0062] S4.2: The black powder precipitate is washed three times with deionized water and ethanol respectively to obtain regenerated graphite, 1.5 times the mass of saturated sodium carbonate as the positive electrode material powder in step S4.1 is added to the primary leachate, stirred at 50°C until no precipitate is generated, and the lithium carbonate precipitate and iron hydroxide are recovered by filtration to obtain a secondary leachate;
[0063] S4.3: Mix the secondary leachate and the extractant in a mass ratio of 1:0.1 and place them in a container. The extractant is a mixed solution of oxalic acid and ethanol in a mass ratio of 1:1. Then place it in a 70°C oil bath and heat until no precipitate is generated. Filter and recover the Co, Ni, and Mn co-precipitates to obtain a tertiary leachate. The tertiary leachate is treated as wastewater and then discharged. Example
[0064] A highly efficient impurity removal and recycling process for lithium-ion batteries, such as Figure 1 As shown, the following steps are included:
[0065] S1: Preparation of efficient leaching agent;
[0066] S1.1: 2 parts by weight of ammonium peroxodisulfate were placed in a container, and then 50 parts by weight of deionized water were added, and magnetic stirring was performed at 30° C. and a stirring speed of 120 rpm until the solid matter in the container was completely dissolved to obtain an ammonium peroxodisulfate solution;
[0067] S1.2: Mix lactic acid and deionized water in a mass ratio of 1:3 and stir evenly to obtain a lactic acid solution. Take 1.5 parts by weight of the lactic acid solution and put it in a dropper, then slowly drop it into the ammonium persulfate solution obtained in step S1.1, while stirring at a stirring speed of 150 rpm. When the lactic acid is completely dropped in, continue stirring for 25 minutes, then add hydrochloric acid to adjust the pH to 4 to obtain a high-efficiency leaching agent.
[0068] S2: Grading of lithium batteries;
[0069] S2.1: Take different types of lithium-ion batteries to be recycled, whose positive electrode materials are lithium iron phosphate, nickel cobalt manganese and lithium cobalt oxide, and whose negative electrode materials are all graphite, and immerse them in a sodium chloride solution with a volume fraction of 6% to decharge until the voltage is less than 2V, and then disassemble them. During disassembly, first remove the plastic iron shell of the lithium-ion battery to be recycled, then separate the positive electrode sheet, the negative electrode sheet and the diaphragm, and centrifuge the remaining mixed material containing the electrolyte and pass it through a 150-mesh sieve to obtain screened waste and organic material;
[0070] S2.2: According to the composition of lithium-ion battery electrolyte, organic solvent and electrolyte liquid are added to the organic material to obtain a new electrolyte product, the plastic iron shell is mechanically crushed and magnetically separated to separate the iron powder for recycling, the diaphragm is heated to remove organic matter and adhesive impurities, and then immersed in clean water for stirring and cleaning, and then ball milling and heating, melt extrusion and granulation are carried out in sequence to recover the diaphragm, and the remaining positive electrode sheets, negative electrode sheets and screened waste are to be processed.
[0071] S3: pretreatment of negative electrode sheet;
[0072] S3.1: Grind the negative electrode plate, pass it through a 220-mesh sieve to obtain black powder, rinse the black powder with deionized water for 4 times, and then dry it at 60°C to obtain cleaned black powder, immerse the cleaned black powder in 3 times the mass concentration of 30% ethylenediamine solution, and stir evenly to obtain a mixed liquid;
[0073] S3.2: The mixed liquid is transferred to a container equipped with a condensation reflux device, and nitrogen is then introduced into the mixed liquid at a flow rate of 80 ml / min for 20 minutes. The heating device is then turned on to heat the mixed liquid at 150°C for 8 hours, and then concentrated to 1 / 4 of the original volume to obtain a black powder pretreatment liquid.
[0074] S4: Recycling of pole piece materials;
[0075] S4.1: The positive electrode sheet and the screened waste are mixed and placed in a grinder for grinding, wherein the mass ratio of the nickel-cobalt-manganese positive electrode, the lithium cobalt oxide positive electrode and the lithium iron phosphate positive electrode is 1:1:1.5, and the positive electrode material powder is obtained after passing through a 200-mesh sieve, and the positive electrode material powder, the black powder pretreatment liquid and the high-efficiency leaching agent are placed in a container at a mass ratio of 1:6:80 and stirred evenly, and then transferred to an oil bath pot and heated at 95°C for 2 hours, and filtered to obtain a black powder precipitate and a primary leachate;
[0076] S4.2: The black powder precipitate is washed 4 times with deionized water and ethanol respectively to obtain regenerated graphite, and saturated sodium carbonate with a mass of 1 times that of the positive electrode material powder in step S4.1 is added to the primary leachate, and stirred at 60°C until no precipitate is generated, and the lithium carbonate precipitate and iron hydroxide are recovered by filtration to obtain a secondary leachate;
[0077] S4.3: Mix the secondary leachate and the extractant in a mass ratio of 1:0.08 and place them in a container. The extractant is a mixed solution of oxalic acid and ethanol in a mass ratio of 1:1. Then place it in a 75°C oil bath and heat until no precipitate is generated. Filter and recover the Co, Ni, and Mn co-precipitates to obtain a tertiary leachate. The tertiary leachate is treated as wastewater and then discharged.
[0078] Comparative Example 1
[0079] Compared with Example 1, the difference of Comparative Example 1 is that, in Comparative Example 1, step S1 is removed, a high-efficiency leaching agent is not prepared, the subsequent high-efficiency leaching agent is replaced with a 4 mol / L HCl solution, and the remaining steps are the same as those of Example 1.
[0080] Comparative Example 2
[0081] Compared with Example 1, the difference of Comparative Example 2 is that step S3 is removed in Comparative Example 2, and the subsequent black powder pretreatment liquid is replaced by grinding the negative electrode plate and passing it through a 200-mesh sieve to obtain black powder, and the remaining steps are the same as those in Example 1.
[0082] Experiment 1: Take the primary leachate obtained in the implementation process of the embodiment, the primary leachate in Comparative Example 1, and the primary leachate in Comparative Example 2, and test the content of each valuable metal ion in the positive electrode powder material and the primary leachate by ICP-OES, and then calculate the leaching rate of each valuable metal ion, leaching rate = content of each valuable metal ion in the primary leachate / content of each valuable metal ion in the positive electrode powder material × 100%, record the data and make a table, as shown in Table 1, it can be seen that the leaching rate of valuable metals in the primary leachate obtained during the implementation of the embodiment is higher than that of Comparative Example 1 and Comparative Example 2, which can prove that the preparation of an efficient leaching agent can greatly improve the leaching rate of metals in the positive electrode material, and it can also be proved that mixing the black powder pretreatment liquid with the positive electrode material powder and the efficient leaching agent can also improve the metal leaching rate.
[0083] Table 1: Leaching rate of each valuable metal ion
[0084] Leaching rate of each valuable metal ion / % Li Ni Co Mn Example 1 98.94 97.13 97.65 95.31 Example 2 98.88 97.12 97.43 94.97 Example 3 99.02 97.31 97.87 95.64 Comparative Example 1 94.23 92.14 93.77 87.6 Comparative Example 2 97.45 96.03 96.29 93.96
[0085] Experiment 2: Take the regenerated graphite obtained in the embodiment and the regenerated graphite in comparative example 2, mix them with conductive carbon black super P and polyvinylidene fluoride in a mass ratio of 8:1:1, and then coat them on the current collector and vacuum dry them at 120℃ for 12h, where the loading amount of the regenerated graphite is 3mg / cm2. With lithium sheet as negative electrode, regenerated graphite as positive electrode, PP as separator, 1M lithium hexafluorophosphate (LiPF6) as electrolyte solute, and a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) with a volume ratio of 1:1 as solvent, assemble into a button cell with a thickness of 2.5mm, the battery test temperature is 27℃, the humidity is less than 30%, and the charge specific capacity of the first cycle of charge and discharge of the regenerated graphite and the charge specific capacity at 200 and 400 cycles are tested and recorded at a current density of 0.1C, and the table is shown in Table 2. It can be seen that the first cycle charging capacity and the charging capacity after the cycle of the regenerated graphite in Example 2 are higher than those of the regenerated graphite in Comparative Example 2, which can prove that the preparation of the black powder pretreatment slurry and the mixed leaching with the positive electrode material powder and the high-efficiency leaching agent can regenerate the waste graphite electrode and have a higher charging capacity and cycle performance.
[0086] Table 2: Charge capacity of the first cycle and after the cycle
[0087] Charging capacity / (mAh / g) First cycle charging capacity Charge capacity after 200 cycles Charge capacity after 400 cycles Example 1 453 443 429 Example 2 451 441 428 Example 3 457 446 431 Comparative Example 2 382 363 341
[0088] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A high-efficiency impurity removal and recycling process for lithium-ion batteries, characterized in that: The following steps are involved: S1: Preparation of efficient leaching agent; ammonium peroxydisulfate and deionized water are mixed and magnetically stirred to prepare an ammonium peroxydisulfate solution, lactic acid is mixed and stirred with deionized water to obtain a lactic acid solution, and the lactic acid solution is slowly dripped into the ammonium peroxydisulfate solution while stirring, and after the dripping is completed, stirring is continued and the pH is adjusted to obtain a high-efficiency leaching agent; S2: Grading of lithium batteries; Taking different types of lithium-ion batteries to be recycled, de-charging and disassembling them to obtain plastic iron shells, positive electrode sheets, negative electrode sheets, diaphragms and a mixture containing an electrolyte, centrifuging the mixture containing the electrolyte and passing it through a mesh sieve to obtain sieved waste and organic materials, supplementing the organic materials with organic solvents and electrolyte liquid to obtain new electrolyte products, crushing the plastic iron shells and magnetically separating them to separate iron powder for recycling, heating and cleaning the diaphragms, and then melt-extruding and granulating them to recover the diaphragms, leaving the positive electrode sheets, negative electrode sheets and sieved waste for processing; S3: pretreatment of negative electrode sheet; The negative electrode sheet is ground and passed through a mesh sieve, then cleaned, and then evenly mixed with an ethylenediamine solution to obtain a mixed liquid, and the mixed liquid is condensed, refluxed, and heated in a nitrogen atmosphere to obtain a black powder pretreatment liquid after concentration; S4: Recycling of pole piece materials; The positive electrode sheet and the screened waste are mixed and ground, and then sieved to obtain positive electrode material powder. The positive electrode material powder, black powder pretreatment liquid and high-efficiency leaching agent are mixed and stirred evenly, and then heated in an oil bath. After filtering, black powder precipitate and primary leaching solution are obtained. The black powder precipitate is washed 3-4 times with deionized water and ethanol respectively to obtain regenerated graphite. Saturated sodium carbonate is added to the primary leaching solution, heated and stirred until no precipitate is generated, and lithium carbonate precipitate and ferric hydroxide are filtered and recovered to obtain secondary leaching solution. The secondary leaching solution and the extractant are mixed and heated in an oil bath, and Co, Ni, and Mn co-precipitates are filtered and recovered to obtain tertiary leaching solution. The tertiary leaching solution is treated as wastewater and then discharged.
2. The high-efficiency impurity removal and recycling process of lithium-ion batteries according to claim 1, characterized in that: Step S1: Preparation of an efficient leaching agent, comprising the following steps: S1.1: 2-3 parts by weight of ammonium peroxodisulfate are placed in a container, and then 50-60 parts by weight of deionized water are added, and magnetic stirring is performed at 25-30° C. and a stirring speed of 100-120 rpm until the solid matter in the container is completely dissolved to obtain an ammonium peroxodisulfate solution; S1.2: Mix lactic acid and deionized water in a mass ratio of 1:(3-4) and stir evenly to obtain a lactic acid solution. Take 1.5-2 parts by weight of the lactic acid solution and put it in a dropper, then slowly drip it into the ammonium peroxydisulfate solution obtained in step S1.1, while stirring at a stirring speed of 120-150rpm. When the lactic acid is completely dripped in, continue stirring for 20-25 minutes, then add a pH adjuster to adjust the pH to 3-4 to obtain a high-efficiency leaching agent.
3. The high-efficiency impurity removal and recycling process of lithium-ion batteries according to claim 2, characterized in that: Step S2: grading of lithium batteries, including the following steps: S2.1: Take different types of lithium-ion batteries to be recycled for de-charging and disassembly. During disassembly, first remove the plastic iron shell of the lithium-ion batteries to be recycled, then separate the positive electrode sheet, the negative electrode sheet and the diaphragm, and centrifuge the remaining mixed material containing the electrolyte and pass it through a 140-150 mesh sieve to obtain sieved waste and organic material; S2.2: According to the composition of lithium-ion battery electrolyte, organic solvent and electrolyte liquid are added to the organic material to obtain a new electrolyte product, the plastic iron shell is mechanically crushed and magnetically separated to separate the iron powder for recycling, the diaphragm is heated to remove organic matter and adhesive impurities, and then immersed in clean water for stirring and cleaning, and then ball milling and heating, melt extrusion and granulation are carried out in sequence to recover the diaphragm, and the remaining positive electrode sheets, negative electrode sheets and screened waste are to be processed.
4. The high-efficiency impurity removal and recycling process of lithium-ion batteries according to claim 3, characterized in that: Step S3: pretreatment of the negative electrode sheet, including the following steps: S3.1: Grind the negative electrode plate, pass it through a 200-220 mesh sieve to obtain black powder, rinse the black powder with deionized water for 3-4 times, and then dry it at 50-60°C to obtain cleaned black powder, immerse the cleaned black powder in 3-5 times the mass concentration of 10-30% ethylenediamine solution, and stir evenly to obtain a mixed liquid; S3.2: Transfer the mixed liquid to a container equipped with a condensation reflux device, and then pass nitrogen into the mixed liquid at a flow rate of 60-80 ml / min for 15-20 minutes, then turn on the heating device to heat at 100-150°C for 6-8 hours, and then concentrate it to 1 / 5-1 / 4 of the original volume to obtain a black powder pretreatment liquid.
5. The high-efficiency impurity removal and recycling process of lithium-ion batteries according to claim 4, characterized in that: Step S4: recycling of the pole piece material, including the following steps: S4.1: The positive electrode sheet and the sieved waste are mixed and placed in a grinder for grinding, and the positive electrode material powder is obtained after passing through a 180-200 mesh sieve. The positive electrode material powder, black powder pretreatment solution and high-efficiency leaching agent are placed in a container at a mass ratio of 1: (6-10): (80-100) and stirred evenly, and then transferred to an oil bath pot and heated at 90-95°C for 1.5-2 hours, and the black powder precipitate and the primary leaching solution are obtained after filtering; S4.2: The black powder precipitate is washed 3-4 times with deionized water and ethanol respectively to obtain regenerated graphite, 1-1.5 times the mass of the positive electrode material powder in step S4.1 is added to the primary leachate, and stirred at 50-60°C until no precipitate is generated, and the lithium carbonate precipitate and iron hydroxide are recovered by filtration to obtain a secondary leachate; S4.3: Mix the secondary leachate and the extractant in a mass ratio of 1:(0.08-0.1) and place them in a container. Then heat them in an oil bath at 70-75℃ until no precipitate is generated. Filter and recover the co-precipitate of Co, Ni and Mn to obtain a tertiary leachate. The tertiary leachate is treated as wastewater and then discharged.
6. The high-efficiency impurity removal and recycling process of lithium-ion batteries according to claim 2, characterized in that: In step S1.2, the pH regulator used to adjust the mixed solution of ammonium peroxodisulfate and lactic acid is hydrochloric acid.
7. The high-efficiency impurity removal and recycling process of lithium-ion batteries according to claim 3, characterized in that: In step S2.1, the different types of positive electrode materials of lithium-ion batteries to be recycled are lithium iron phosphate, nickel cobalt manganese and lithium cobalt oxide, and the negative electrode materials are all graphite.
8. The high-efficiency impurity removal and recycling process of lithium-ion batteries according to claim 3, characterized in that: The de-charge operation in step S2.1 is to immerse the lithium-ion battery to be recycled in a sodium chloride solution with a volume fraction of 4-6% until the voltage is less than 2V.
9. The high-efficiency impurity removal and recycling process of lithium-ion batteries according to claim 5, characterized in that: Step S4.1 The mass ratio of the nickel-cobalt-manganese positive electrode, the lithium cobalt oxide positive electrode and the lithium iron phosphate positive electrode in the positive electrode sheets disassembled from different types of lithium-ion batteries to be recycled is 1:1:(1.5-2).
10. The high-efficiency impurity removal and recycling process of lithium-ion batteries according to claim 5, characterized in that: In step S4.3, the extractant is a mixed solution of oxalic acid and ethanol in a mass ratio of 1:1.
Citation Information
Patent Citations
Recovery method of waste lithium iron phosphate positive electrode material
CN112441572A
A process for recovering cobalt ion, nickel ion and manganese ion from metal-containing residues
EP3950977A1